The Microbial Olympics. - Youle, M; Rohwer, F; Stacy, A; Whiteley, M; Steel, B; Delalez, N; Nord, A; Berry, R; Armitage, J; Kamoun, S; Hogenhout, S; Diggle, S; et al. (2012)
Every four years, the Olympic Games plays host to competitors who have built on their natural talent by training for many years to become the best in their chosen discipline. Similar spirit and endeavour can be found throughout the microbial world, in which every day is a competition to survive and thrive. Microorganisms are trained through evolution to become the fittest and the best adapted to a particular environmental niche or lifestyle, and to innovate when the 'rules of the game' are changed by alterations to their natural habitats. In this Essay, we honour the best competitors in the microbial world by inviting them to take part in the inaugural Microbial Olympics.